2013
DOI: 10.1038/srep01834
|View full text |Cite
|
Sign up to set email alerts
|

Zhang-Rice physics and anomalous copper states in A-site ordered perovskites

Abstract: In low dimensional cuprates several interesting phenomena, including high Tc superconductivity, are deeply connected to electron correlations on Cu and the presence of the Zhang-Rice (ZR) singlet state. Here, we report on direct spectroscopic observation of the ZR state responsible for the low-energy physical properties in two isostructural A-site ordered cuprate perovskites, CaCu3Co4O12 and CaCu3Cr4O12 as revealed by resonant soft x-ray absorption spectroscopy on the Cu L3,2- and O K-edges. These measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
7
36
0
Order By: Relevance
“…While the valence of Cu remains 2 + (3 d 9 ) with hole doping, there is a clear emergence of a ligand hole state (3 d 9 L ) on the oxygen site, which is important for Cooper pairing4243. Detailed examination of the bulk cuprates have shown that this peak on both the Cu L -edge and O K -edge track directly with doping of the CuO 2 plane4445, which can be altered in the bulk by changing oxygen stoichiometry31, replacing Y with Ca4647, or doping at Cu sites48.…”
Section: Resultsmentioning
confidence: 99%
“…While the valence of Cu remains 2 + (3 d 9 ) with hole doping, there is a clear emergence of a ligand hole state (3 d 9 L ) on the oxygen site, which is important for Cooper pairing4243. Detailed examination of the bulk cuprates have shown that this peak on both the Cu L -edge and O K -edge track directly with doping of the CuO 2 plane4445, which can be altered in the bulk by changing oxygen stoichiometry31, replacing Y with Ca4647, or doping at Cu sites48.…”
Section: Resultsmentioning
confidence: 99%
“…The PFY-XA spectrum exhibits, as expected, two pronounced peaks representing the Cr L 3 and L 2 edges. 28,29 The TEY-XA spectrum that was recorded simultaneously as the PFY-XA spectrum, on the other hand, presents a flat line with no distinguishable Cr features, suggesting that the embedded species is not detectable by the TEY method. The TEY investigation of a standalone membrane by measuring sample drain current, as shown in the lower panel of figure 3, further corroborates this conclusion.…”
mentioning
confidence: 99%
“…Perovskite materials with a formula of ABO 3 , where the A cation is 12-fold coordinated and the B cation is 6-fold coordinated with the oxygen, have been interested in various applications such as catalysis, energy, environment and bioscience applications131415161718. Recently, noble methods for preparation of perovskite with unique architecture and morphology have emerged in the form of porous, scaffold, and egg-shell skeleton due to their high geometric surface area with large cavities, light weight and flexibility for mass and heat transfer1920212223.…”
mentioning
confidence: 99%